Secretor Status Strongly Influences the Incidence of Symptomatic Norovirus Infection in a Genotype-Dependent Manner in a Nicaraguan Birth Cohort. (15th June 2021) - Reyes, Yaoska; González, Fredman; Gutiérrez, Lester; Blandón, Patricia; Centeno, Edwing; Zepeda, Omar; Toval-Ruíz, Christian; Lindesmith, Lisa C; Baric, Ralph S; Vielot, Nadja; Diez-Valcarce, Marta; Vinjé, Jan; et al.
Abstract: Background: The role of histo-blood group on the burden and severity of norovirus gastroenteritis in young infants has not been well documented. Methods: Norovirus gastroenteritis was assessed in 443 Nicaraguan children followed from birth until 3 years of age. Stool samples were tested for norovirus by reverse-transcription quantitative polymerase chain reaction (RT-qPCR), and histo-blood group antigens (HBGAs) were determined by phenotyping of saliva and blood. Hazard ratios and predictors of norovirus acute gastroenteritis (AGE) outcome stratified by HBGA were estimated using Cox proportional hazards models. Results: Of 1353 AGE episodes experienced by children, 229 (17%) tested positive for norovirus with an overall incidence of 21.9/100 child-years. Secretor children were infected as early as 2 months of age and had a higher incidence of norovirus GII compared to nonsecretor children (15.4 vs 4.1/100 child-years, P = .006). Furthermore, all GII.4 AGE episodes occurred in secretor children. Children infected with GI (adjusted odds ratio [aOR], 0.09 [95% confidence interval CI, .02–.33]) or non-GII.4 viruses (aOR, 0.2 [95% CI, .07–.6]) were less likely to have severe AGE compared to GII.4-infected children. Conclusions: Secretor status in children strongly influences the incidence of symptomatic norovirus infection in a genogroup or genotype-dependent manner and provides evidence that clinical severity in children depends on norovirus genotypes. Abstract : In a Nicaraguan birth cohort, the norovirus incidence was 21.9/100 child-years with the secretor phenotype strongly influencing the incidence of symptomatic norovirus infection in a genogroup or genotype-dependent manner. The study further provides evidence that clinical severity in children depends on norovirus genotypes.